2019
DOI: 10.1186/s12872-019-1065-8
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression are associated with physical inactivity but not modified by gender or the presence of a cardiovascular disease; a cross-sectional study

Abstract: Background Depressive symptomatology may act as a barrier to enhance physical activity. This phenomenon is predominantly found in patients with an established cardiovascular disease (CVD) and in female patients. This cross-sectional study investigated (1) the association between symptoms of depression and physical inactivity, and (2) whether this association is different between primary and secondary prevention patients, and between men and women. Methods The study desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…34 Our results partially agree with those from other studies. 11,32 Achttien et al 11 showed that there was an association between symptoms of depression and lower levels of physical activity, without any difference between men and women (n = 1250; mean age 73.9 ± 6.9 years). In a study without stratification according to sex, Ludwig et al 32 found a positive association between depressive symptoms and insufficient physical activity, regardless of sociodemographic and behavioral factors, or BMI.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…34 Our results partially agree with those from other studies. 11,32 Achttien et al 11 showed that there was an association between symptoms of depression and lower levels of physical activity, without any difference between men and women (n = 1250; mean age 73.9 ± 6.9 years). In a study without stratification according to sex, Ludwig et al 32 found a positive association between depressive symptoms and insufficient physical activity, regardless of sociodemographic and behavioral factors, or BMI.…”
Section: Discussionmentioning
confidence: 98%
“…The association between depressive symptoms and insufficient levels of physical activity that was found in the present study is consistent with previous studies showing an inverse relationship between depressive symptoms and physical activity. 11,32 It is known that the association between depressive symptoms and physical activity may be bidirectional. Hence, physical activity is considered to be a healthcare strategy for reducing the risk of developing depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Moreover, a lack of PA is a substantial risk factor for developing depressive symptoms. 13 The literature has suggested that there is a significant relationship between depressive symptoms and physical inactivity 14 and a 2-fold risk of depressive symptoms in inactive people compared to those who engage in regular PA. 15…”
Section: Introductionmentioning
confidence: 99%